2019
DOI: 10.1007/s13364-018-00413-2
|View full text |Cite
|
Sign up to set email alerts
|

Ecology of a versatile canid in the Neotropics: gray foxes (Urocyon cinereoargenteus) in Belize, Central America

Abstract: Your article is protected by copyright and all rights are held exclusively by Mammal Research Institute, Polish Academy of Sciences, Bia#owie#a, Poland. This e-offprint is for personal use only and shall not be selfarchived in electronic repositories. If you wish to self-archive your article, please use the accepted manuscript version for posting on your own website. You may further deposit the accepted manuscript version in any repository, provided it is only made publicly available 12 months after official p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 34 publications
(57 reference statements)
1
11
0
Order By: Relevance
“…Deciduous, mixed forest, and total forest cover The total size of each of wet forest, deciduous forest, and mixed forest, from Homer et al (2020) Grey foxes are often associated with various forest habitats (Allen et al, 2021;Borchert, 2012;Davis et al, 2011;Harmsen et al, 2019) p Deciduous, mixed forest, and total forest edge…”
Section: Coyote Abundancementioning
confidence: 99%
See 1 more Smart Citation
“…Deciduous, mixed forest, and total forest cover The total size of each of wet forest, deciduous forest, and mixed forest, from Homer et al (2020) Grey foxes are often associated with various forest habitats (Allen et al, 2021;Borchert, 2012;Davis et al, 2011;Harmsen et al, 2019) p Deciduous, mixed forest, and total forest edge…”
Section: Coyote Abundancementioning
confidence: 99%
“…Grey foxes are associated with a diversity of habitats throughout their range, with the one constant being a positive correlation with forested areas (Allen et al, 2021). Grey foxes often use forests that are open (Borchert, 2012) and have a preference for edge habitat (Davis et al, 2011;Harmsen et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies found weak or no association with forest-related covariates including forest cover (Rich et al 2018), canopy cover (Davis et al 2011;Reed 2011), distance to nearest forest (LeFlore et al 2019), or basal area (Barrett et al 2012) perhaps reflecting insufficient covariate variability within the study area or regional variation in habitat associations. Results from several studies suggest that these foxes may use more open forest environments (Barrett et al 2012;Borchert 2012), edge habitats (Davis et al 2011;Deuel et al 2017;Harmsen et al 2019;Pearman-Gillman et al 2020), and heterogenous landscapes (Cooper et al 2012;Lesmeister et al 2015; but see Constible et al 2006). Despite the methodological variation across studies, our review highlights the importance of forest environments for Grey Foxes across their range.…”
Section: Habitatmentioning
confidence: 99%
“…Cotton rat predators in this region include mesocarnivores, raptors, and snakes 25 . Mesocarnivores include coyotes ( Canis latrans ), foxes ( Vulpes vulpes and Urocyon cinereoargenteus ), raccoons ( Procyon lotor ), Virginia opossums ( Didelphis virginiana ), nine-banded armadillos ( Dasypus novemcinctus ), striped skunks ( Mephitis mephitis ), and bobcats ( Lynx rufus ), although opossums, armadillos, and skunks are unlikely to present much risk to cotton rats 26,3942 . The snake community in this region is diverse.…”
Section: Methodsmentioning
confidence: 99%